Comparative Expression Analysis of Putative Cancer Stem Cell Markers CD44 and ALDH1A1 in Various Skin Cancer Subtypes. Issue 1 (2016) - Erfani, Elham; Roudi, Raheleh; Rakhshan, Azadeh; Sabet, Mehrdad Nasrollahzadeh; Shariftabrizi, Ahmad; Madjd, Zahra
Introduction: Skin cancers, particularly melanoma, are initiated and maintained by a subpopulation of tumor cells expressing stemness markers that are called cancer stem cells (CSCs). This study aimed to evaluate the expression levels and clinicopathological significance of the putative CSC markers CD44 and ALDH1A1 in patients with skin cancer. Methods: The expression levels of CD44 and ALDH1A1 were investigated in 107 skin cancer specimens including 58 (54%) basal cell carcinomas (BCC), 37 (35%) squamous cell carcinomas (SCC), and 12 (11%) melanomas using the tissue microarray (TMA) technique. The correlation of the expression levels of these markers and clinicopathological parameters was then analyzed. Results: The expression levels of CD44 and ALDH1A1 were significantly higher in melanoma patients than patients with SCC or BCC (p<0.001 and p = 0.002, respectively). A higher level of CD44 expression was more often found in melanoma tumor cells with a higher rate of recurrence (p = 0.029) and in SCC cases with ulceration (p = 0.01), while there was no significant correlation between ALDH1A1 expression and other clinicopathological parameters. Similarly, coexpression of CD44 and ALDH1A1 (CD44 high /ALDH1A1 high ) was significantly observed in melanoma samples (p<0.001). Conclusions: These findings suggest that a CD44 high /ALDH1A1 high phenotype in melanoma and a CD44 high phenotype in SCC can be considered candidates for targeted therapy of skin cancers aiming at CSCs.